2019
DOI: 10.7752/jpes.2019.s3118
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Cluster-set training may decrease the rating of perceived exertion (RPE) responses during resistance training when compared to the traditional training. This decrease in RPE scores may influence the increase in pleasure levels associated with exercise without affecting the adaptive responses to training. Thus, the purpose of this study was to compare the effect of two different strength training methods (Traditional vs. Cluster-set) on pleasure and rating perceived exertion (RPE) in trained men. Twelve trained… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…Strength training studies on pleasure are still inconclusive [7,11,12,31,32]. In a study involving trained men, Portugal et al [12] observed a decrease in pleasure only when the high-intensity (80% 1RM) group was compared with the control group (without exercise).…”
Section: Discussionmentioning
confidence: 99%
“…Strength training studies on pleasure are still inconclusive [7,11,12,31,32]. In a study involving trained men, Portugal et al [12] observed a decrease in pleasure only when the high-intensity (80% 1RM) group was compared with the control group (without exercise).…”
Section: Discussionmentioning
confidence: 99%